Pengaruh Gaya Hidup Islami Dan Harga Terhadap Keputusan Pembelian Mie Samyang Pada Mahasiswa S1 Ekonomi Islam Universitas Negeri Surabaya Angkatan 2018–2020 - Irfansyah, Fikri; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2022)
The purpose of this study was to determine the effect of Islamic lifestyle and price on purchasing decisions for samyang noodles in S1 Islamic Economics students, State University of Surabaya class 2018 - 2020 and determine the variables that have a dominant influence on the dependent variable. This study uses a causal associative method with a descriptive quantitative approach. The variables used are Islamic lifestyle (X1), price (X2), and purchasing decisions (Y). The population of this study were undergraduate students of Islamic Economics, State University of Surabaya from class 2018 to 2020. The data that the researcher used was primary data by collecting data through online questionnaires via google forms which were then distributed through social media. Respondents' answers were measured using a Likert scale. The results of this study indicate that simultaneously has a positive effect on purchasing decisions. This is evidenced by the value of Fcount > Ftable (98,857 > 3.15), thus indicating the influence of Islamic lifestyle and price simultaneously on purchasing decisions. Meanwhile, it also partially influences purchasing decisions. This is indicated by the Islamic lifestyle variable (X1) which has a regression coefficient of 4.454 > 1.998, and the price variable (X2) which has a regression coefficient of 5.896 > 1.998. So partially, it shows that there is a positive and significant influence of these two variables on purchasing decisions..